Intrapreneurs: Essential to Building Healthy Academic Communities - Irena Yashin-Shaw; Dianne Morrison-Beedy (The Ohio State University Libraries, 2022)
Background: Intrapreneurialism is emerging as a powerful force for enhancing organizational transformation and viability in a post-pandemic world. It is the enfranchisement and empowerment of people, liberating them to engage their enterprising talent in the service of creating value for the benefit of the organization (Yashin-Shaw, 2018). Aim: For the purposes of this article, the notion of a healthy academic community refers to the long-term viability, robustness, and relevance of the institution. Being able to foster future success in the face of exponential change is a hallmark of a resilient organization (Duchek, 2020). In this sense, a healthy academic community is one where the institution and its stakeholders can thrive in the face of unprecedented disruptive change and unexpected conditions by adapting appropriately (Burnard, Bhamra, & Tsinopoulos, 2018). The traditional form and function of higher education are being challenged as new technologies are democratizing access to knowledge, learning, and credentialing. A diversity of higher education options have emerged for students beyond the traditional university (Marshall, 2018). Such challenges can pose an existential threat to universities.   Results: How can academic communities thrive in the face of these rapid changes? The answer is to liberate and engage the enterprising talent of staff, students, faculty, and the extended community associated with the institution, whether local or global, physical or virtual. Enterprising employees, who think and act like entrepreneurs, are called intrapreneurs. Conclusion: By embracing and supporting intrapreneurs at all levels, academic communities will be well placed to flourish in the new post-pandemic world.